Air pollution and ST-elevation myocardial infarction treated with primary percutaneous coronary angioplasty: A direct correlation. (1st June 2017) - Zuin, Marco; Rigatelli, Gianluca; dell'Avvocata, Fabio; Picariello, Claudio; Conte, Luca; Marcantoni, Lina; Cardaioli, Paolo; Zuliani, Giovanni; Roncon, Loris
Abstract: Purpose: The relationships between air pollutant concentration levels and admission for primary percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI) have never been assessed. Methods: We retrospectively reviewed 4 consecutive years of medical and instrumental data (1st January 2012 to 1st March 2016) to identify patients admitted with STEMI and subsequently treated with primary PCI in our third referral center. Daily atmospheric pressure data (in hectopascal [hPa]) and air pollutant concentration levels were obtained from the regional meteorological service which had a monitoring site in our city (Rovigo, Italy). Pollutants investigated were nitrogen dioxide (NO2 ), particulate matter ≤ 10 μm (PM10 ), ozone (O3 ), sulfur dioxide (SO2 ) and carbon monoxide (CO). Safety air concentration levels for the air pollutants were also considered. Results: PCI in STEMI patients was more frequent when AP was higher than 1013.15 hPa (61.8% vs 38.2%, p  < 0.001). The incidences of STEMI patients when NO2, PM10 and O3 levels overcame the safe threshold were 83.1%, 52% and 8.5%, respectively. A positive correlation was found between the daily number of STEMI subsequently treated with primary PCI and the air pollutant levels of the same day for NO2 ( r  = 0.205, p  = 0.001), PM10 ( r  = 0.349, p  < 0.0001) and O3 ( r  = 0.191, p  = 0.002). Conclusions: A direct and significant correlation exists between the number of daily STEMI patients and the NO2, PM10 and O3 air concentration levels of the same day.